Hubungan Keadaan Sosial Ekonomi dan Konsumsi Ikan dengan Status Gizi Anak di Desa Sukajaya Lempasing, Kabupaten Pesawaran, Lampung : The Relationship Between Socio-economic Status and Fish Consumption with Nutritional Status of Children in Sukajaya Village, Lempasing, Pesawaran District, Lampung - Nurulhaq, Fauziah; Riyadi, Hadi; Aries, Muhammad (Jurnal Ilmu Gizi dan Dietetik, 2022)
Rapid growth and development occur in school-age children. To deal with this, efforts that improve fish consumption in the community are expected to increase children's nutritional intake. In connection with this, this study aimed to analyze the relationship between socio-economic status and fish consumption with nutritional status of children in Sukajaya village. The design of this study was a cross-sectional study with 61 subjects who were selected by purposive sampling. This study was conducted in December-January 2021 at Sukajaya village in Lampung. There was no significant correlation between the contribution of fish protein to the level of protein adequacy (p>0.05). Nutritional status had no relationship with the amount of fish consumption (p>0.05). The results revealed that the relationship between fish consumption and socio-economic characteristics showed no significant relationship (p>0.05) between father's education, parent income, and family size. However, there was a significant relationship between fish consumption and maternal education (p<0.05). There was no significant relationship between nutritional status and socio-economic characteristics (p>0.05).